Kidney failure among patients with Takotsubo syndrome or myocardial infarction: a retrospective analysis - Bill, Verena; El-Battrawy, Ibrahim; Kummer, Marvin; Mügge, Andreas; Aweimer, Assem; Behnes, Michael; Akın, Ibrahim (Journal of cardiovascular development and disease, 2022)
Background: Takotsubo syndrome (TTS) is a syndrome with ambiguous pathophysiology. Impaired kidney function (KF) seems to impact the outcome of patients with TTS. We hypothesized that KF worsens the outcome among TTS patients and furthermore, TTS patients with concomitant KF experience more adverse events compared to myocardial infarction (MI) patients with concomitant KF. Methods and Results: This retrospective single-center study comprised two groups (cohorts) of patients including patients with TTS and concomitant KF (n = 61, 27.1%) and patients with MI and concomitant KF (n = 164, 72.9%). The clinical outcomes were delineated as short-term outcomes defined as in-hospital adverse events during index hospitalization and long-term outcomes defined as adverse events over five-year clinical follow-ups. All-cause mortality, stroke, cardiopulmonary resuscitation (CPR), life-threatening arrhythmias, need for respiratory support, and cardiogenic shock with subsequent use of inotropic agents during index hospitalization were denoted as in-hospital adverse events. All-cause mortality, rehospitalization due to heart failure, stroke, thromboembolic events, and the recurrence of primary pathology (TTS and MI) were analyzed during five-year follow-ups after index hospitalization. A higher mortality rate was noted among TTS patients with KF compared to TTS without KF. In addition, in-hospital event rates in patients with TTS and concomitant KF compared to MI and concomitant KF were comparable with the exception of a higher rate of respiratory support in TTS patients. The mortality rate was significantly higher among patients with TTS and KF at 4 years (29.5% vs. 15.9%, p = 0.02) and 5 years (34.4% vs. 20.7%, p = 0.03) in comparison to patients with MI and concomitant KF. In contrast, the rate of re-hospitalization related to heart failure was higher at 30 days, and at one-, four-, and five-year follow-ups in patients suffering from MI and KF compared to TTS and concomitant KF. Additionally, the recurrence of MI after 4 and 5 years was higher than the recurrence of TTS (4.9% vs. 15.2%; 4.9% vs. 16.5%). There were no differences in life-threatening arrhythmias and stroke in both groups. Conclusions: Patients with TTS and concomitant KF have higher all-cause mortality when compared to MI and concomitant KF. The mechanisms responsible remain to be determined.
Dieser Artikel gehört zum Special issue: Takotsubo syndrome, Short QT syndrome and Brugada syndrome
Gesehen am 08.01.2024